2018
DOI: 10.1093/icesjms/fsy020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating habitat, prey, and mesopredator associations in a community of marine birds

Abstract: Offshore wind energy development on the US Atlantic Continental Shelf has brought attention to the need for marine spatial planning efforts to reduce potential conflict between wind turbines and marine animals, including seabirds. We evaluated the effects of marine mammals, fishes, and habitat characteristics on the distribution and relative abundance of marine birds off the coast of Delaware, Maryland, and Virginia. From May 2012 to 2014, we collected line transect data from 14 shipboard surveys, and novel hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Environmental data were examined for differences among years using non-parametric Wilcoxon tests. The number of birds in the 4 km 2 bins contained a large number of zeros (> 70% of bins yr −1 ); thus, we used a zeroaltered (hurdle) negative binomial model (pscl package; Zeileis et al 2008) to determine the important predictor variables underlying the distribution of each shearwater species, similar to Nishizawa et al (2015) and Goyert et al (2018). The hurdle model is composed of 2 parts: a binomial-based part, which identifies the factors explaining presence (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental data were examined for differences among years using non-parametric Wilcoxon tests. The number of birds in the 4 km 2 bins contained a large number of zeros (> 70% of bins yr −1 ); thus, we used a zeroaltered (hurdle) negative binomial model (pscl package; Zeileis et al 2008) to determine the important predictor variables underlying the distribution of each shearwater species, similar to Nishizawa et al (2015) and Goyert et al (2018). The hurdle model is composed of 2 parts: a binomial-based part, which identifies the factors explaining presence (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to this interannual variability (especially for GRSH), we were interested to examine how the predictor variables explaining the presence and number of GRSH and SOSH differed among years; thus, we ran separate models by year, as other similar studies have done (e.g. Ainley et al 2009, Goyert et al 2018. The by-year models were initially run with an interaction between the number of the other Shearwater × Prey density, but the interaction was not statistically significant; therefore, the interaction was omitted from the by-year analysis but was left in the full model (with year as a discrete random variable; see Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interspecific interactions may provide additional opportunities for socially flexible and opportunistic predators. The pelagic realm is a dynamic environment where prey aggregations (e.g., bait balls) can attract multiple predators that engage in facilitative (e.g., commensal) or competitive feeding frenzies (Goyert et al, 2018; Goyert, Manne, & Veit, 2014). During these social interactions, predatory fishes (e.g., tunas) and marine mammals can drive prey upwards towards seabirds feeding at the air–sea interface (Safina, 1990; Veit & Harrison, 2017).…”
Section: Role As Preymentioning
confidence: 99%
“…Further research efforts should explore overwinter survival of juvenile herring as climate conditions change and explore whether other forage fish species (such as pollock or capelin) can mediate variation in herring abundance for marine predators. Additional research should also incorporate community dynamics that have been found to influence predator–prey relationships in other systems, such as local enhancement and interactions with marine mammals (e.g., Anderwald, Evans, Gygax, & Hoelzel, 2011; Fauchald, 2009; Goyert et al, 2018; Viet & Harrison, 2017). Further understanding of these relationships will facilitate the identification of critical areas and time periods for marine birds and their prey and may increase our insight of the status of the marine ecosystem.…”
Section: Discussionmentioning
confidence: 99%